Design and Numerical Simulation of the Performance of Acoustic Plenum Chamber of a Marine Gas Turbine Air Supply System - RASOULIMOGHADAM, Mehrdad; KHERADMAND, Saeid (Archives of Acoustics, 2019)
In the present work, an approach to obtain a design method for the size of the plenum chamber cross-section of a marine gas turbine air supply system has been investigated. Flow in ducts makes noise which is very high in the turbine inlet part because of the large amount of flow. Therefore, this phenomenon should be considered in the design process. A suitable approach to design the duct is proposed (considering acoustic and aerodynamic performance at the same time). In this method, an air supply channel system of the marine gas turbine has been categorized into three sections according to the requirements of the aerodynamic and acoustic; inlet, plenum chamber, and outlet channels with circular cross-sections. The geometrical dimensions of inlet and outlet channels have been determined using the plane waves theory about a channel, in which the effects of flow is ignored. Space limitations of battleships at the dominant frequency have been considered. Then, the optimized size of the mid-channel section, in terms of both aerodynamic and acoustic requirements, using numerical methods and regarding the effects of flow has been calculated. Various 3D turbulent flows inside the plenum chamber have been considered, in which large eddy simulation turbulence model is utilized. Ffowcs, Williams and Hawkings models are used for the sound propagation process based on the Lighthill integral equation. The validity of the simulation has been checked by comparing results (sound pressure level) with experimental data obtained from a chamber. The comparison revealed the acceptable errors for a variety of frequencies. The results disclosed that the performance of channel system aerodynamic decreased when the fraction of plenum chamber cross-section to inlet/outlet channel cross-section increased. With an increase in the cross-section size at first Acoustic performance is improved and then worsen. Six different cases of marine gas turbine air supply system configurations have been presented, in which the limitation of the battleship space is considered. Examining and comparing the acoustic performance of different cases of the air supply channel system, it was found that the amount of sound pressure level, around the air supply channel system, and the high-pressure sound area can move along the air supply channel system. Additionally, deviations from plane waves considering the effects of flow have been inspected in all cases. The reason for this deviation is the effects of the airflow through the channel system and quadrupole sources in the production of sound in the channel system, which causes higher modes.